Drug repositioning as a therapeutic strategy for neurodegenerations associated with OPA1 mutations. (24th November 2020) - Aleo, Serena J; Del Dotto, Valentina; Fogazza, Mario; Maresca, Alessandra; Lodi, Tiziana; Goffrini, Paola; Ghelli, Anna; Rugolo, Michela; Carelli, Valerio; Baruffini, Enrico; Zanna, Claudia
Abstract: OPA1 mutations are the major cause of dominant optic atrophy (DOA) and the syndromic form DOA plus, pathologies for which there is no established cure. We used a 'drug repurposing' approach to identify FDA-approved molecules able to rescue the mitochondrial dysfunctions induced by OPA1 mutations. We screened two different chemical libraries by using two yeast strains carrying the mgm1 I322M and the chim3 P646L mutations, identifying 26 drugs able to rescue their oxidative growth phenotype. Six of them, able to reduce the mitochondrial DNA instability in yeast, have been then tested in Opa1 deleted mouse embryonic fibroblasts expressing the human OPA1 isoform 1 bearing the R445H and D603H mutations. Some of these molecules were able to ameliorate the energetic functions and/or the mitochondrial network morphology, depending on the type of OPA1 mutation. The final validation has been performed in patients' fibroblasts, allowing to select the most effective molecules. Our current results are instrumental to rapidly translating the findings of this drug repurposing approach into clinical trial for DOA and other neurodegenerations caused by OPA1 mutations.